A Study on Political Awareness and Approach of Youth Towards Voting in Kashmir - Bilal Ahmad Bhat; Ronika Yousuf; Tanzeela Habib; Ifrah Rashid; Nazia Fayaz Azad; Aasifa Akhter (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Worldwide youth spend a lot of time on social media which has become a powerful source of information that converts automatically into knowledge. In current study, we chose 400 youth at random on their consent using stratified random sampling procedure and with the help of self-developed validated questionnaire, we examine the political awareness and approach of youth Kashmir towards voting. The data collected was analysed using standard statistical tools. It was found that majority of respondents understudy were aware of politics and political scenario of the study area. Statistically, there was non-significant difference in general in the awareness and approach of youth towards voting between male and female youth in Kashmir. The study showed that 79.5% respondents cast vote as they consider it their right, 67.5% respondents reported that people cast vote as they feel it is the agent of change, 81.5% respondents reported that people cast vote as every vote counts and 32.5% people reported that people cast just for fun without thinking on it seriously. Majority of respondents male as well as female were not satisfied with the performance of candidates irrespective of any political party. Further, group discussion with elders revealed that handful of corrupt people who had no sympathy with their mother land or people of Kashmir spoiled the image of Kashmiri people for their personal benefits. The people in power were enjoying life because of their dual policy. The current study was based on sample of 400 youth, it was suggested that future study on this topic may be conducted on large sample.